Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Perusahaan Kimia Farma Tbk dan PT Indofarma Tbk Periode waktu 1 Tahun - rizky ismail (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2023)
Company performance is a picture of the achievements that the company achieved in a certain period. The company's financial performance can be seen from the financial statements of the current year or year. previously which is usually created as a guideline for the following year. In general, financial performance is an effort made by the company in measuring and assessing every success achieved in making a profit, so that the company can see the prospects, growth, and development potential that have been achieved in the company. This study aims to determine the comparison of the financial performance of PT. Kimia Farma Tbk, and PT. Indofarma Tbk. By comparing similar companies, it can be determined whether the good and bad financial performance is based on financial ratios, with a difference test, it can be seen whether there is a difference between pt. Indofrma and Kimia Farma. Then it's seen who's bigger on average. The ratios used include liquidity ratio, solvency ratio, profitability ratio, activity ratio. The research sample is 2 companies from the pharmaceutical sector that are considered the most stable in. profit gains. Data collection method is secondary data obtained from financial statements on the Indonesia Stock Exchange. The purpose of this study is to see the comparison of the company's performance of PT Indofarma and PT Kimia Farma in terms of the value of the financial ratio. The results of this study show that there are not significant differences between PT Indofarma and PT Kimia Farma